2006
DOI: 10.1016/j.mri.2006.01.003
|View full text |Cite
|
Sign up to set email alerts
|

In vivo 13C NMR spectroscopy and metabolic modeling in the brain: a practical perspective

Abstract: In vivo 13 C NMR spectroscopy has the unique capability to measure metabolic fluxes noninvasively in the brain. Quantitative measurements of metabolic fluxes require analysis of the 13 C labeling time courses obtained experimentally with a metabolic model. The present work reviews the ingredients necessary for a dynamic metabolic modeling study, with particular emphasis on practical issues. D

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
151
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 96 publications
(153 citation statements)
references
References 47 publications
2
151
0
Order By: Relevance
“…The most commonly studied nuclei are 1 H, 31 P, and 13 C, although nuclei from isotopes of many other elements (e.g., 2 H, 6 Li, 10 B, 11 B, 14 N, 15 N, 17 O, 19 F, 23 Na, 29 Si, 35 Cl, 113 Cd, 129 Xe, 195 Pt) have been used in high-field NMR spectroscopy [3]. Overall, the frequency at which a specific nucleus resonates depends on the external magnetic field strength applied, the gyromagnetic ratio of the nucleus, and its chemical environment.…”
Section: Basics Of Heteronuclear Nmr Signalmentioning
confidence: 99%
See 1 more Smart Citation
“…The most commonly studied nuclei are 1 H, 31 P, and 13 C, although nuclei from isotopes of many other elements (e.g., 2 H, 6 Li, 10 B, 11 B, 14 N, 15 N, 17 O, 19 F, 23 Na, 29 Si, 35 Cl, 113 Cd, 129 Xe, 195 Pt) have been used in high-field NMR spectroscopy [3]. Overall, the frequency at which a specific nucleus resonates depends on the external magnetic field strength applied, the gyromagnetic ratio of the nucleus, and its chemical environment.…”
Section: Basics Of Heteronuclear Nmr Signalmentioning
confidence: 99%
“…It is thus primordial to choose the appropriate substrate according to the technique (mainly direct and indirect 13 C MRS) and the need for an increased signal relative to cost. After glycolysis, carbon positions 1 and 6 of glucose will label the methyl group of pyruvate, leading primarily to the labeling of glutamate C4 following the pyruvate dehydrogenase pathway and glutamate C2 for the pyruvate carboxylase pathway [23]. [1, 6-13 C] glucose is thus twice as efficient as [1][2][3][4][5][6][7][8][9][10][11][12][13] C] glucose labeling, and thus detecting, TCA cycle aminoacids.…”
mentioning
confidence: 99%
“…However, such a long infusion experiment is not always compatible with the maintenance of a proper physiology under euglycemia or hyperglycemia, or with the tolerance of the subject, in particular for human studies. A good compromise has to be found for the experimental time, since an accurate measurement of the metabolites 13 C enrichment over a duration compatible with glutamate/ glutamine turnover rates is essential to ensure accuracy and robustness in neuro-glial modelling, as distinct detection of C3 and C2 turnover curves is critical in distinguishing the glial compartment metabolism [43,48]. Dynamic experimental data of the temporal evolution of the 13 C-enriched metabolites (Fig.…”
Section: In Vivo 13 C Mrs In Mice: Overview Of a General Experimentsmentioning
confidence: 99%
“…For example, distinctions between glutamatergic and GABAergic fluxes require measurement of 13 C turnover from Glc and acetate into glutamate, glutamine, and GABA (Pfeuffer et al, 1999). The ingredients necessary for a dynamic metabolic modeling in such case are discussed in a review by Henry et al (2006). By using 13 C NMR spectroscopy in anesthetized rats, explicitly combining [1-13 C]glucose and [2-13 C]acetate infusion with three-compartment metabolic modeling, Patel et al (2005) showed recently that total neurotransmitter cycling (Vcyc(tot)) could be resolved into separate glutamatergic (Vcyc(glu)) and GABAergic (Vcyc(GABA)) components.…”
Section: Major Findings and Implicationsmentioning
confidence: 99%